Foreign direct investment, agglomerations and demonstration effects: an empirical investigation - Frank Barry; Holger Görg; Eric Strobl (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2001)
Many previous studies have shown that the localisation of firms can be an important factor in attracting new foreign direct investment into a host country. What has been missing in this literature thus far, however, is an investigation into the reasons why industry clusters attract firms. We distinguish between “efficiency agglomerations” as firms locating close to each other because they can increase their efficiency by doing so, and “demonstration effects”, whereby existing firms send signals to new investors as to the reliability of the host country and newly entering firms follow previous firms. In this paper we try to disentangle these two effects, by examining the location of US and UK firms in Ireland. We calculate proxies for “efficiency agglomerations” and “demonstration effects” and include these proxies in an empirical model of the location decision of firms. For US firms, we find that both efficiency agglomeration and demonstration effects are important determinants of entry. For UK firms, however, the evidence is not as clear cut.
Keywords: 330; Direktinvestition; Amerikanisch; Betriebliche Standortwahl; Agglomerationseffekt; Irland